2003
DOI: 10.1016/s1607-551x(09)70459-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zirconia‐Modified Magnesia Investment on the Casting of Pure Titanium

Abstract: Several investigations have examined magnesia-based investments for pure titanium casting. However, the thermal expansion value was insufficient at low casting temperatures and high interfacial reactivity occurred at high casting temperatures. The purpose of this investigation was to modify a magnesia-based investment by adding a heat-resistant mold material, zirconia, in different ratios to produce a more accurate titanium casting. The thermal expansion value was measured using a new precise automatic laser r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…An analysis of variance procedure indicated that the key variables in casting superconductive ceramics are the particle size distribution and sintering temperature. Additionally, the interactions between the sintering temperature and the other process parameters also found to influence the density, porosity, and critical current density of the fired ceramics [3]. The thermal expansion value was insufficient at low casting temperatures and high interfacial reactivity occurred at high casting temperatures.…”
Section: Introductionmentioning
confidence: 98%
“…An analysis of variance procedure indicated that the key variables in casting superconductive ceramics are the particle size distribution and sintering temperature. Additionally, the interactions between the sintering temperature and the other process parameters also found to influence the density, porosity, and critical current density of the fired ceramics [3]. The thermal expansion value was insufficient at low casting temperatures and high interfacial reactivity occurred at high casting temperatures.…”
Section: Introductionmentioning
confidence: 98%
“…14 Some researchers highlighted that IC has the ability to manufacture a wide range of industrial components with near net shape. 15,16 Conventional IC process starts with formation of wax pattern in precisely machined die to maintain dimensional accuracy. Patterns are attached to a riser and the resulting tree is stucco coated and kept to dry in air-controlled environment.…”
Section: Introductionmentioning
confidence: 99%
“…5 IC is used for the production of numerous equipments like dental tools, electrical equipments, electronics, radar, guns, hand tools, jewellery, machine tools, material handling equipments, metal working equipments, agricultural equipments, cameras and pneumatics/hydraulics components, etc. 6–8 The IC process involves 12 steps as illustrated in Figure 1. Various researchers have investigated the effect of primary slurry parameters on the plate weight (ceramic retention test) in ceramic shell IC process.…”
Section: Introductionmentioning
confidence: 99%